Comparative Response of Biosensing Platforms Based on Synthesized Graphene Oxide and Electrochemically Reduced Graphene. Issue 1 (7th December 2012) - Casero, E.; Alonso, C.; Vázquez, L.; Petit‐Domínguez, M. D.; Parra‐Alfambra, A. M.; de la Fuente, M.; Merino, P.; Álvarez‐García, S.; de Andrés, A.; Pariente, F.; Lorenzo, E.
Abstract In this work, we report the synthesis and characterization of different kinds of graphene nanomaterials and their applicability to the development of biosensing platforms. We have synthesized graphene oxide (GO) following a modified Hummer's method, which has been subsequently reduced by electrochemical procedures. This reduction strategy precludes the employment of toxic solvents, leading to a product, electrochemically reduced graphene (ERG), free of contaminants. The characterization of the synthesized nanomaterials has been performed by different techniques such as X‐ray diffraction spectroscopy (XRD), Raman spectroscopy, X‐ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and atomic force microscopy (AFM). The information gathered by this combination of techniques confirms that i) the synthesis methodology affords the production of GO nanosheets, which present a typical lateral dimension of several hundreds of nanometers and a thickness value of 1.3±0.1 nm, ii) the reduction step has been successfully achieved leading to graphene nanosheets free of oxygen functionalities with an average lateral dimension of at least 1 micrometer and a thickness value of 2.8±0.2 nm. Once we have confirmed that both materials have been successfully synthesized, we have studied the effect of the effect of their inclusion in biosensing platforms on the analytical response, selecting a lactate oxidase based biosensor as a model system. We have demonstrated that although the incorporation of GO or ERG to the device results in an enhancement of the analytical response of the resulting biosensing platform, the former system offers slightly better analytical properties and a more reproducible response than the ERG one.